1992
DOI: 10.1002/1097-0142(19921201)70:11<2631::aid-cncr2820701111>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation-fibrinolysis system and markers of collagen metabolism in lung cancer

Abstract: Background. Evidence suggests that the fibrinolysis system and peritumoral connective tissue play important roles in tumor spread. Methods. In this study, the authors evaluated the following parameters in 30 consecutive patients with lung cancer: thrombin‐antithrombin complex (TAT), cross‐linked fibrin split products D‐dimer (DD), plasmin‐alpha2‐antiplasmin inhibitor complex (PAP), and two antigens related to connective tissue, the aminoterminal propeptide of type III procollagen (PIIIP) and the 7s domain of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…The elevated prechemotherapy TAT levels in advanced breast cancer patients in this study support previous findings in breast (Falanga et al, 1998;Donati and Falanga, 2001), lung (Gabazza et al, 1992;Seitz et al, 1997) and colorectal cancer (Iversen et al, 1996;Iversen and Thorlacius-Ussing, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The elevated prechemotherapy TAT levels in advanced breast cancer patients in this study support previous findings in breast (Falanga et al, 1998;Donati and Falanga, 2001), lung (Gabazza et al, 1992;Seitz et al, 1997) and colorectal cancer (Iversen et al, 1996;Iversen and Thorlacius-Ussing, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Both Pectasides and Canobbio (Canobbio et al, 1986;Pectasides et al, 1999) show shortening of functional clotting assay times equivalent to our 3-month findings. In lung cancer patients receiving chemotherapy, Gabazza et al (1992) reports an early shortening of APTT (at days 2, 5 and 7 following treatment) and a slightly later shortening of PT (at days 5, 7 and 14 following treatment). The fact worthy of note in the current study is that the shortening of APTT is more pronounced in the group subsequently developing VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of D-dimer may, in fact, indicate a host compensatory response to the increased formation of cross-linked fibrin [5,11], as indicated by the finding of a concomitant activation of the coagulation pathway in NSCLC [2][3][4][5][6]. Indeed, in a recent study we have shown that D-dimer levels are increased in NSCLC concomitantly to thrombin/anti-thrombin III complexes (TATc), an activation marker of coagulation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the tendency of clotting and fibrinolytic disorders to develop in patients with malignancy [1,2] The clinical presentation of thrombotic alterations in cancer patients may vary from the classic picture of consumptive coagulopathy or thromboembolism to low-grade intravascular coagulation [3,4]. Specific conditions associated with cancer, such as stasis due to prolonged immobilization, surgery, infections, vascular endothelium injury due to chemotherapeutic agents, and abnormalities of the blood coagulation system, contribute to the hypercoagulable and thrombophilic state of patients with cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%